The Influence of Transformational Leadership Style on Job Satisfaction and Employee Performance - Tamawiwy, Shani Reinaldi; Edastama, Primasatria (Forum Kerjasama Pendidikan Tinggi, 2024)
With the changes that occur in the leadership style applied to an organization that impacts and affects the entire organization, such as changes in job satisfaction to employee performance. Where, these changes have a good or opposite effect on the organization, such as an increase or decrease in the performance of employees in the organization. The purpose of this study is to determine whether the Transformational Leadership Style of a leader applied to the organization will have an impact that affects Job Satisfaction and Employee Performance at the Sulawesi River Basin 1 government agency. This research was conducted on employees with status as Civil Servants at the Sulawesi River Basin 1 in Manado, North Sulawesi with a total of 149 employees. The Structural Equation Model-Partial Last Square (SEM-PLS) is a quantitative methodology used in this research that employs the causality association method. The study's findings indicate that, first, a transformational leadership style significantly and favorably affects job satisfaction with p-values below 0.05 (P = 0.000 <0.05. Second, employee performance is positively and significantly impacted by transformational leadership style with the p-values below 0.05 (P = 0.004 < 0.05). Lastly, there is a significant positive correlation between employee performance and job satisfaction is also accepted since the value of this relationship is below 0.05 (P = 0.000 < 0.05). Thus, it is envisaged that the organization's management will be able to use and enhance the transformational leadership style to an even greater degree and will also be able to pay closer attention to the performance and working conditions of workers.